Enhancing learning through technology - Sorensen, Elsebeth Korsgaard; O Murchu, Daithi (Gale virtual reference library, 2006)
"This book identifies and presents the latest research on theory, practice, and capturing learning designs and best-practices in education"--Provided by publisher.